Riesgo crediticio y sobreendeudamiento de las MiPymes de la Agencia MIBANCO de Canto Rey-distrito de San Juan de LuriganchoLima Metropolitana, periodo 2017 - 2019 - Dianderas Quiñones, Angel Valois (2020)
The main objective of this research is to determine the relationship between credit risk and over-indebtedness of the MSMEs of the Agencia MIBANCO de Canto ReySan Juan de Lurigancho-Lima Metropolitana period, 2017-2019, the purpose of this research is carried out, due that it is decisive to know and establish different technology processes whose factors can affect mimicking the risk of late payment in relation to the credits financed to the MSMEs with guidelines and systems established in order to generate greater financial utility for the Agency, this work has been carried out with a quantitative approach, applied type of non-experimental design and descriptive-correlational level. In this investigation we worked with the financial statements of the agencies of the 3 different periods. The data base and matrix instrument was developed, which was analyzed with the SPSS statistical program, descriptive statistics and inferential statistics methods were applied to evaluate the behaviors of the variables, reason for which the correlational variables were analyzed using method R Pearson's conclusion concluding with the p value = 0.736, which supports the acceptance of the null hypothesis for being greater than 0.05 and rejects the alternative hypothesis, which indicates that there is no relationship between credit risk and over-indebtedness of MSMEs evaluating the behavior of same of which by theoretical research if there is a relationship between both determined variables.